2021
DOI: 10.1161/strokeaha.120.031668
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cerebrovascular Events With COVID-19 Infection

Abstract: Background and Purpose: Coronavirus disease 2019 (COVID-19) has been associated with an increased incidence of thrombotic events, including stroke. However, characteristics and outcomes of COVID-19 patients with stroke are not well known. Methods: We conducted a retrospective observational study of risk factors, stroke characteristics, and short-term outcomes in a large health system in New York City. We included consecutively admitted patients with acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 35 publications
4
67
2
3
Order By: Relevance
“…In our retrospective series, 1.9% (n = 105) of the 5469 COVID-19 patients admitted to our health system during March and April were diagnosed with stroke [49]. The majority of COVID-19 positive stroke patients suffered ischemic stroke (79.1%) followed by 15.2% intracerebral hemorrhage, 3.8% subarachnoid hemorrhage, and 1.9% transient ischemic attack.…”
Section: Concerning Early Observationsmentioning
confidence: 88%
“…In our retrospective series, 1.9% (n = 105) of the 5469 COVID-19 patients admitted to our health system during March and April were diagnosed with stroke [49]. The majority of COVID-19 positive stroke patients suffered ischemic stroke (79.1%) followed by 15.2% intracerebral hemorrhage, 3.8% subarachnoid hemorrhage, and 1.9% transient ischemic attack.…”
Section: Concerning Early Observationsmentioning
confidence: 88%
“…The fact that patient has recovered near fully from neurological standpoint also supports vascular inflammation-related event rather than underlying cardiac issues. [7][8][9] Of note, patient did have a venous catheter in place in the right cavoatrial junction at the time of developing the jugular vein thrombi; however, it does not explain why she would develop bilateral thrombosis. Of note, CT angiography of the neck was attempted but was a poor study, hence, could not determine if there was clot propagation from one side of the neck to the other.…”
Section: Discussionmentioning
confidence: 97%
“…Ischemic stroke is a rare but known manifestation of COVID-19 [6]. One large retrospective study shows that the incidence of the stroke in COVID-19 patients is slightly more than 1%, but cannot be ignored [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that patients who are COVID-19 positive were more likely to have a cryptogenic cause of stroke when compared to COVID-19 negative patients, suggesting an association of COVID-19 disease with stroke [6,7]. This association of COVID-19 disease with acute ischemic stroke is likely secondary to multiple factors as SARS CoV-2 has been postulated to cause endothelial damage, severe cytokine release, generalized hypercoagulability, as well as direct cytopathic effect on the central nervous system [6][7][8]. Hypercoagulability is one of the features of pathogenesis of COVID-19 disease [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation